1. Modeling electrochemical impedance spectroscopy results of Cu andThiosemicarbizide−Boron Nitride nano-sheets electrodes in 3.5wt% NaCl solution, based on an electrochemical reaction mechanism - Barraza-Fierro, Jesus Israel; Galicia, Monica; López-Martínez, Héctor; Vázquez–Gómez, Octavio; Cruz-Mejía, Héctor; Villalobos, Julio Cesar (2023)
The corrosion behavior of copper and copper-functionalized boron nitride nanocomposites (Cu-BNNS) was studied in a 3.5 wt.% NaCl solution. Polarization curves and cyclic voltammetry experiments were used to differentiate the various stages of corrosion behavior. Additionally, electrochemical impedance spectroscopy (EIS) was used to understand the different steps in the degradation mechanism. The EIS results were analyzed using adsorption models at open circuit potential and at a bias potential of 250 mV, and different reaction kinetics parameters were quantified. During the first hour of immersion, the formation of CuCl increased on the Cu-BNNS, where the reaction constant for the formation of adsorbed CuCl was lower in the impedance model. However, on the Cu electrode, CuCl was not formed during the first hour, and the reaction constant was higher. The proposed model is consistent with the experimental observations from cyclic voltammetry, polarization, and scanning electron microscopy.